Resections and reconstruction of the trachea - Nin Vivo, Jorge; Salsamendi, María; Bertullo, Hugo; Brandolino, Mario; Eschapasse, Henry (Cirugía del Uruguay, 1983)
Tracheal surgery offers every day better theraeuic psibilities. A well trained surgical team is ny to perform it. In order to assure.a correct venlaion during the operation is important the obion between nesthesist and surgeon. A s sil plai must be stablished taking in to nt he coect opportunity, a precise approach do como ma redonda l XXXI Congreso Uruguayo de . Monedeo, Noiembre de 1980. rof. o nno e Aatomía, Fac. Med. Montevideo. Cno de Tórx del M.S.P. Prof. Aregado de Aniolo&ía, Fac. Med. Monteideo. Cijanos de tóx, Hosp. Sint Bois, M.S.P. Montevideo. Prof. de Clruda de Tóx Y Cariovculr. Centro Hosplier Univerllre, Tolose, Frnca.• Dirección: Luis P. Ponce 1324/601, Montevideo (Dr. J. Nin Vivo). and a sufficient exposition, without any compromise of tracheal irrigation. The limits of tracheal esection are done by the necessity of avoiding any tension at the suture leve!. When the extension of the tracheal resection does not allow to perform a primary suture, to avoid tension, it may be necee-· sary to perform maneuvers that allow the drop of the larynx or techniques of mobilization and bronchial reconstruction. We believe that for more extended resections, have to be considered the ue of Silastic prosthesis. For non-resectable tumors, we have employed the Montgomery tracheal "T" tube, _ with_god _resuls and excellent tolerance.